Creation and manipulation of surface code defects with quantum optimal control - Raii, Omar; Dey, Anirban; Mintert, Florian; Burgarth, Daniel (Physical Review A, 2025)
The surface code is a stabilizer code whose ground space degeneracy depends on defects in the lattice. The protocols developed to create defects in the system have previously relied on adiabatic dynamics. In this work we use techniques of quantum optimal control to overcome the requirement for adiabaticity and achieve defect creation and implemention of other important operations required for topological quantum computation at much faster timescales.
CRIS-Team Scopus Importer:2025-01-31